Colombia : Creditor Rights and Insolvency Proceedings - Rouillon, Adolfo (World Bank, Washington, DC, 2012)
This article analyzes the legislation and institutions connected with creditor rights and insolvency proceedings in Colombia. It aims to contribute to the debate on the conditions required to restore the vitality of the Colombian credit environment. In relation to creditor rights, there is a particular emphasis on mechanisms for establishing security interests used in granting corporate credit. The analysis identifies the principal factors affecting the efficiency of security interests. These include deficiencies in substantive and procedural law, as well as in registry organization. The paper goes on to analyze the legal, institutional and regulatory framework for insolvency proceedings, identifying weaknesses and highlighting strengths that insolvency reforms should aim to preserve. The need for attention to corporate workouts and prepackaged reorganization agreements is also addressed. The paper concludes with prioritized recommendations for a plan of legal and institutional reform intended to improve the credit environment, creditor protection and enable the establishment of a more balanced insolvency system. Applying the recommendations to Senate Bill 207/05 (Insolvency Regime) makes it possible to identify the strengths of the Bill, as well as refinements that might be considered so as to reduce the legal uncertainty, which limits the growth of banking credit in Colombia, and to achieve a reduction in credit costs, particularly for small and mid-sized companies.